Variable resolution coding with JPEG 2000 part 10 - Gamito, M. N.; Dias, J. (Proc. SPIE 5558, Applications of Digital Image Processing XXVII, 2004)
JPEG 2000 Part 10 is a new work part of the ISO/IEC JPEG Committee dealing with the extension of JPEG 2000 technologies to three-dimensional data. One of the issues in Part 10 is the ability to encode non-uniform data grids having variable resolution across its domain. Some parts of the grid can be more finely sampled than others in accordance with some pre-specified criteria. Of particular interest to the scientific and engineering communities are variable resolution grids resulting from a process of adaptive mesh refinement of the grid cells. This paper presents the technologies that are currently being developed to accommodate this Part 10 requirement. The coding of adaptive mesh refinement grids with JPEG 2000 works as a two step process. In the first pass, the grid is scanned and its refinement structure is entropy coded. In the second pass, the grid samples are wavelet transformed and quantized. The difference with Part 1 is that wavelet transformation must be done over regions of irregular shape. Results will be shown for adaptive refinement grids with cell-centered or corner-centered samples. It will be shown how the Part 10 coding of an adaptive refinement grid is backwards compatible with a Part 1 decoder.